2011
DOI: 10.1108/17440081111165901
|View full text |Cite
|
Sign up to set email alerts
|

Identifying commonalities in web content management system engineering

Abstract: Purpose -The main purpose of this paper is to improve a web content management system (WCMS) product line for future implementations by identifying software commonalities in WCMS-based web applications. WCMS plays a central role in modern web application development: most large public and internal web sites are based on a WCMS foundation. If we can improve the implementation process, the effectiveness and efficiency of web application development will increase significantly. Design/methodology/approach -This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…He suggested that future research should look into the issues of personalization of content over different platform. Jurriaan Souer, Joor, Helms, and Brinkkemper (2011) also work on identifying software commonalities in order to improve the implementation of content management system and products.…”
Section: Technology Dimensionsmentioning
confidence: 99%
“…He suggested that future research should look into the issues of personalization of content over different platform. Jurriaan Souer, Joor, Helms, and Brinkkemper (2011) also work on identifying software commonalities in order to improve the implementation of content management system and products.…”
Section: Technology Dimensionsmentioning
confidence: 99%
“…WebManager (Souer, Joor, Helms, & Brinkkemper, 2011;van Berkum, Brinkkemper, & Meyer, 2004) builds on standard technologies and products (e.g., Java, Apache Tomcat, Apache Felix, SQL) that can be scaled easily. This enables the gradual extension of the OME from a small research prototype to a publicly available resource.The OME depends on various WebManager services, merges with its user interface, and builds on the underlying repository.…”
Section: Development Viewmentioning
confidence: 99%